Bacterial Etiology and Antibiotic Resistance Patterns in Neonatal Sepsis in Tehran during 2006-2014 - Fatemeh Haj Ebrahim Tehrani; Mohammad Moradi; Narjes Ghorbani (Iranian Society of Pathology, 2017)
Background & Objective: Neonatal sepsis is one of the leading causes of mortality in neonatology wards. The aim of this study was to assess sepsis pathogens and antibacterial resistance patterns in a teaching hospital during seven years in Tehran, Iran. Methods: In this retrospective study, all neonates suspected to sepsis and fulfilling the sepsis criteria admitted to NICU ward of Mustafa Khomeini Hospital, Tehran, Iran during 2007 to 2014 were included. Demographic information, blood test results, blood culture results of neonates and antibiogram findings were extracted from their documents. Data was analyzed using SPSS 15. Results:Ninety neonates with positive culture test were included. Fifty-three were male (58.9%). Thirty neonates were delivered vaginally (33.3%) and 60 caesarean section (66.7%). Most bacterial growths in culture were Staphylococcus aureus and E. coli. The rates of resistance for antibiotics like ceftriaxone, cefotaxim and gentamycin were 5%, 30% and 15%, correspondingly. There were 15 cases (16.7%) with resistance to imipenem. Conclusion: Antibacterial resistance patterns vary in different parts of the world and even within a country, therefore assessing resistance patterns in a region is of great importance for proper management and treatment. Our findings might help physicians for proper selection of antibiotics for treatment of neonatal sepsis.